Dialogare: compendio di fisica - Lima, Manuela (Strumenti per la didattica e la ricerca, 2017)
This compendium represents a starting point for those who wish to review the main topics of Physics in view of the admission tests to the scientific faculties. The main purpose of the text is to intrigue the reader, invite them to ask questions about the world around us and provide them with the basic skills to face the admission test to the University, serenely and with the appropriate competence. This is not a book and it is certainly not exhaustive, but it remains consistent with the topics proposed in the admission tests. The volume is divided into 8 parts which deal with the main topics that students face during secondary school: kinematics, dynamics, fluids, gas, thermodynamics, electrostatics, geometric optics and waves. Each topic is accompanied by multiple choice questions with frequently commented answers. The complexity in the presentation of the topics is weighed on the knowledge that a student leaving the secondary school should have acquired during the course of their studies.